PSGL-1: a novel immune checkpoint driving T-cell dysfunction in obstructive sleep apnea - Díaz-García, Elena; García-Sánchez, Aldara; Alfaro, Enrique; López-Fernández, Cristina; Mañas, Eva; Cano-Pumarega, Irene; López-Collazo, Eduardo; García-Río, Francisco; Cubillos-Zapata, Carolina (Frontiers in Immunology, 2023)
Introduction Although higher incidence of cancer represents a major burden for obstructive sleep apnea (OSA) patients, the molecular pathways driving this association are not completely understood. Recently, the adhesion receptor P-selectin glycoprotein-1 (PSGL 1) has been identified as a novel immune checkpoint, which are recognized major hallmarks in several types of cancer and have revolutionized cancer therapy. Methods The expression of PSGL-1 and its ligands VISTA and SIGLEC-5 was assessed in the leucocytes of OSA patients and control subjects exploring the role of intermittent hypoxia (IH) using in vitro models. In addition, PSGL-1 impact on T-cells function was evaluated by ex vivo models. Results Data showed PSGL-1 expression is upregulated in the T-lymphocytes from patients with severe OSA, indicating a relevant role of hypoxemia mediated by intermittent hypoxia. Besides, results suggest an inhibitory role of PSGL-1 on T-cell proliferation capacity. Finally, the expression of SIGLEC-5 but not VISTA was increased in monocytes from OSA patients, suggesting a regulatory role of intermittent hypoxia. Discussion In conclusion, PSGL-1 might constitute an additional immune checkpoint leading to T-cell dysfunction in OSA patients, contributing to the disruption of immune surveillance, which might provide biological plausibility to the higher incidence and aggressiveness of several tumors in these patients.